Proceedings of the Sixth European Conference on Software Maintenance and Reengineering
DOI: 10.1109/csmr.2002.995797
|View full text |Cite
|
Sign up to set email alerts
|

Non-functional integration and coordination of distributed component services

Abstract: 1The integration of distributed services has been identified as one of the most important challenges of E-business technology. A great deal of progress has been made in the development of methods and techniques for the integration of distributed components but most of the solutions tends to focus on the problem of syntactical and semantical compatibility of the functional services provided or required by the components. Although the non-functional properties of the services are equally important, because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The events that are not filtered, such as NFR failures, are forwarded to the (global) event system. Events are mainly consumed by the configuration manager, which interprets the NADL XML description and executes the necessary actions, for more details refer to [11] [16].…”
Section: Frodica Management Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The events that are not filtered, such as NFR failures, are forwarded to the (global) event system. Events are mainly consumed by the configuration manager, which interprets the NADL XML description and executes the necessary actions, for more details refer to [11] [16].…”
Section: Frodica Management Systemmentioning
confidence: 99%
“…FRODICA and its environment have been presented in details previously in [15] [11] and the present work build from that experience and proposes a new management system, which is more intelligent' and reactive in supporting dynamic reconfiguration. In this direction we have investigated several approaches to supporting intelligent adaptation and reconfiguration.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some recent developments in the standarisation of interface definition aim to simplify system composition such as XML, its recent extension ebXML [11], and a language called Xelha [2]. These focus on the issues of multimedia quality properties, data formats and interoperability, but do not address the integration of nonfunctional properties [12].…”
Section: Related Workmentioning
confidence: 99%
“…The premise is that dynamic changes in the system software architecture at runtime can increase adaptability. Further study has also shown that those changes can provide increased adaptability when they support monitoring and tuning of the system's non-functional requirements [Ribeiro-Justo 2002]. After all, the architecture incorporates and is home to all non-functional requirements.…”
Section: Introductionmentioning
confidence: 98%